1976
DOI: 10.1029/ja081i007p01453
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary magnetic fields, their fluctuations, and cosmic ray variations

Abstract: The cause of Forbush decreases is examined by using neutron monitor data and measurements of the interplanetary magnetic field. It is found that for the period examined (December 15, 1965, to April 23, 1966), large enhancements of the interplanetary magnetic field correlate well with decreases in cosmic ray intensity, while various parameters connected with the fluctuations in the field do not display such good correlation. The inference is drawn that Forbush decreases are not related to the turbulence or rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…All the above points are in agreement with the summary of Forbush decrease characteristics presented by Barouch and Burlaga [1975] and Barouch and Sari [1976] on the basis of a statistical study.…”
Section: From (1) and (5) We See That The Diffusion Coefficient Depensupporting
confidence: 90%
“…All the above points are in agreement with the summary of Forbush decrease characteristics presented by Barouch and Burlaga [1975] and Barouch and Sari [1976] on the basis of a statistical study.…”
Section: From (1) and (5) We See That The Diffusion Coefficient Depensupporting
confidence: 90%
“…Barouch and Burlaga [11] found that the individual magnetic enhancements are generally associated with depressions in cosmic ray intensity, and Barouch and Sari [12] have further demonstrated that these depressions are not related to turbulence or random motions in the field and only the large-scale features of interplanetary magnetic fields are important. However, Nishida [13] has emphasized the importance of scattering by the turbulent magnetic field in producing the transient modulation.…”
Section: Introductionmentioning
confidence: 96%